2019
DOI: 10.52547/nkums.11.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses' Clinical Competency in Imam Hasan Hospital, Bojnurd, Iran

Abstract: Introduction: Nursing is as a clinical profession that is improving day to day. One of the important problem at hospitals is that nursing management are not aware of the competency of new entrance nurses. So, this study was done to assess competency of new nurses Emam Hasan hospital at Bojnurd. Methods: This study was the first stage of an action research. Nurses with under 10 working years were selected by census sampling. Task-based checklists based on profession nursing task, 13 clinical competencies were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The lower CP score of emergency ward nurses is attributed to patients staying in the emergency ward for a short period and to the high turnover of nurses in this ward. Whenever nurses are required to perform tasks outside the scope of their nursing responsibilities, as directed by their managers, they are prevented from focusing on their primary duties (21).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The lower CP score of emergency ward nurses is attributed to patients staying in the emergency ward for a short period and to the high turnover of nurses in this ward. Whenever nurses are required to perform tasks outside the scope of their nursing responsibilities, as directed by their managers, they are prevented from focusing on their primary duties (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the results of a study by Bahreini et al in Shiraz showed that nurses' competence in both the level and frequency of using competencies is excellent in the clinical settings of this hospital (19); nevertheless, another study by Bahreini et al in Bushehr showed that nurses' CC was unfavorable in education/guidance and quality assurance (26). Additionally, the results of evaluating the CC of nursing personnel in Bojnord showed that the CC of this personnel is in good condition (21).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations